ANALISIS PENGARUH LIFESTYLE, KUALITAS PELAYANAN DAN PERCEIVED VALUE TERHADAP CUSTOMER VALUE UNTUK MENINGKATKAN MINAT BELI KONSUMEN PADA APARTEMEN DI SEMARANG (Studi Pada Mg.Suites Apartemen, Star Apartemen dan The Parama Graha Apartemen di Kota Semarang ) - Aria Dewi, Astarina; Soesanto, Harry (Faculty of Economics and Business Diponegoro University, 2015)
The problem in this research is still a lot of people of semarang and outside of semarang choose to buy a house than with the apartment .This research aims to test the power of lifestyle quality of services and perceived value to customer value to improve consumer purchasing interest in an apartment in semarang (study in the mg.suites apartment , apartment star and parama graha apartment). This study using three independent variable is lifestyle , the quality of services and perceived value , variable interest then buy the consumer as an independent variable variable variable customer value as of intervening.A method of this research technique using probability sample that is random sampling and clusters of sampling to sample as many as 121 of respondents in the middle class and over who had bought an apartment in semarang .A method of data analyst using a technique double regression analysis , the analysis includes: test the validity of , a test of reliability , test the assumption of the classics , linear regression test doublet test , test f , test the coefficients determined and test sobel.The results show significantÂ and positive effect lifestyle to customer value, significant and positive effect service quality to customer value, significant and positive effect perceived value to customer value, and then significant and positive effect customer value to purchase intention.